Efektivitas Penegakan Hukum Kekerasan Seksual di Indonesia dan Urgensi Pembentukan Badan Nasional Penanganan Terpadu - Ika Damayanti; Sri Wahyu Handayani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Sexual violence is a serious crime that has significant impacts on victims physically, psychologically, and socially. Although Indonesia has established several legal regulations governing the handling of sexual violence, the effectiveness of law enforcement in such cases still faces various challenges. This study aims to analyze the effectiveness of law enforcement regarding sexual violence cases in Indonesia and to examine the urgency of establishing a specialized institution focused on addressing these crimes. This research employs a normative legal research method using statutory and conceptual approaches through the analysis of the Law on Sexual Violence Crimes, the Criminal Code, and the Law on Witness and Victim Protection. The results indicate that normatively the legal framework for handling sexual violence in Indonesia is relatively comprehensive, however its implementation still encounters several obstacles such as weak coordination among law enforcement institutions, low reporting rates of cases, and limitations in the victim protection system. The discussion also shows that several countries have developed specialized institutions or units that handle sexual crimes in an integrated manner, which improves the effectiveness of law enforcement. Therefore, this study concludes that establishing a specialized institution dedicated to handling sexual violence in an integrated system could become a strategic step to strengthen law enforcement mechanisms and improve protection for victims in Indonesia.